Contextual Meanings Used by Archibald McLeish’s Poetry ‘The Young Dead Soldiers do Not Speak’ - Irawati Anita Dewi (JournEEL, 2019)
This study was conducted by the aim to investigate the contextual meaning applied in the poetry written by McLeish by the title “The Young Dead Soldiers Do Not Speak”. This research applied descriptive qualitative design by applying the semantics theory supported by theory of contextual meaning proposed by Leech (1981). The instrument was the researcher as the primary instrument of the study. The data were indentified, classified, displayed, and were described into the poetry in regard the contextual meaning. The findings showed: (1) This poetry was one of Archibald MacLeish contribution towards World War II because the function of the poetry is not only commemorated the dead, but also made it clear that those who survived bore a special responsibility to make the deaths of these soldiers meaningful; (2) The poetry was a portrayed of horrific World War I in Europe which was pointed out Archibald MacLeish got the record because he was a volunteer of the United State of America young soldiers whom sent to Europe to serve his country; and (3) The dead soldiers saw the peace toward their death because they gave their life for the country so they did not die for nothing. Nevertheless, their dead seem nothing if the further generations do not remember them as the piece of peace which have to be honored.